2021
DOI: 10.1155/2021/5592132
|View full text |Cite
|
Sign up to set email alerts
|

Binary Bitwise Artificial Bee Colony as Feature Selection Optimization Approach within Taguchi’s T-Method

Abstract: Taguchi’s T-Method is one of the Mahalanobis Taguchi System- (MTS-) ruled prediction techniques that has been established specifically but not limited to small, multivariate sample data. The prediction model’s complexity aspect can be further enhanced by removing features that do not provide valuable information on the overall prediction. In order to accomplish this, a matrix called orthogonal array (OA) is used within the existing Taguchi’s T-Method. However, OA’s fixed-scheme matrix and its drawback in copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The objective function of the proposed T-method with the NIBBA algorithm is to maximize the integrated estimate SNR value, which returns the optimal combination of input features. The selection of the final optimal feature combination is based on the 50% and more feature appearance in the optimal combination of every run, as practiced in [14].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective function of the proposed T-method with the NIBBA algorithm is to maximize the integrated estimate SNR value, which returns the optimal combination of input features. The selection of the final optimal feature combination is based on the 50% and more feature appearance in the optimal combination of every run, as practiced in [14].…”
Section: Experimental Designmentioning
confidence: 99%
“…The result shows an improvement in prediction accuracy as compared to the conventional OA approach. In a different study, Harudin et al [14] utilized a modified artificial bee colony algorithm with a binary bitwise operator as the feature selection approach, and the outcome recorded an enhancement in prediction accuracy. These studies have shown practicality in employing metaheuristic algorithms as the T-method feature selection optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Ramlie et al [40] concluded that none of the four thresholding methods outperformed one over the others in (if it is not for all) most of the datasets. Harudin et al [41] proved that incorporating Bitwise Artificial Bee Colony (BitABC) techniques into Taguchi's T-Method methodology effectively improved prediction accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to [38], none of the four thresholding approaches outperformed the others in almost all of the datasets. [39] showed that combining Bitwise Artificial Bee Colony (BitABC) methods along with Taguchi's T-Method greatly improved the accuracy of predictions.…”
Section: Introductionmentioning
confidence: 99%